Interactive Note Taking: Understanding Erving Goffman and Dramaturgy - Yarosh, Jerrod (TRAILS: Teaching Resources and Innovations Library for Sociology, 2024)
Students engage in an in-class learning experience where they work through a structured note taking activity that allows them to be introduced, learn, apply, and review course material related to Erving Goffman and Dramaturgy. The general idea is that students are given a handout with a blank person outline and associated content areas to take notes related to Goffman’s ideas (i.e., areas of presentation, types of participants in interaction, impression management, props, scripts and spoiled presentations). Students are instructed to think about a career that they would like to pursue or their ideal job and draw and color the person outline to fit with their idea. Students then work through as a class a structured activity covering each section on the handout going over the definitions, providing examples of each, and adding to the person outline through additional drawings of the various terms being covered related to their person’s occupation.